Filsafat Dalam Sistem Nilai Pancasila - Windari, Sri; Aziz, Muhammad Ilham (Indonesian Journal Publisher, 2021)
This paper examines philosophy in the Pancasila value system. This research can be qualified in philosophical research, the method used in this research is qualitative research method through literature review. The type of method used is descriptive qualitative. While the data analysis technique, the writer uses the technique introduced by Miles and Huberman, which includes data reduction, presentation, and conclusion. This article begins with the formulation of the meaning of philosophy in the Pancasila system. Then describe descriptively related to the function of philosophy in the Pancasila system. Pancasila is the basis as well as the ideology of the Indonesian nation, which can be implemented in the life of the nation and state. While philosophy can be understood as a way of deep thinking to get a truth. Philosophy in the Pancasila system is a philosophy on the basis of the state which consists of five precepts as derivations that have their respective roles, but the goal is the same, namely to manage and realize the values contained in it in the life of the nation and state in Indonesia. Each of the precepts contained in Pancasila is basically a unity that cannot be separated and interrelated. The five precepts as the basis of the philosophy of the Indonesian state are each a representation of the civilization of the Indonesian nation.